2022
DOI: 10.1007/s11259-022-10009-6
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection patterns of vector-borne zoonotic pathogens in owned free-ranging dogs in central Chile

Abstract: We investigated the co-occurrence of the nine of the most relevant canine vector-borne pathogens (CVBP) using conventional and real-time PCR and evaluated risk factors and potential non-apparent haematological alterations associated with co-infection in 111 rural, owned, free-ranging dogs in the Metropolitan Region of Chile.At least one pathogen was detected in 75% of the dogs. DNA of Anaplasma platys (Ap; 36%), Candidatus Mycoplasma haematoparvum (CMhp; 31%), Mycoplasma haemocanis (Mhc; 28%), Trypanosoma cruz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…The current research revealed that young dogs had a higher chance of being infected with CVBPs than adult dogs, which corroborated another study of dogs in central Chile [ 32 ]. There are several potential reasons why young dogs may be more susceptible to CVBP infection compared to adult dogs.…”
Section: Discussionsupporting
confidence: 91%
“…The current research revealed that young dogs had a higher chance of being infected with CVBPs than adult dogs, which corroborated another study of dogs in central Chile [ 32 ]. There are several potential reasons why young dogs may be more susceptible to CVBP infection compared to adult dogs.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding filarial nematodes, Alcaíno et al ( 16 ) reported a prevalence of 29.9% in dogs from the north, center, and south of Chile (excluding Región del Maule), with 99.4% of infections attributed to the genus Dipetalonema (currently Acanthocheilonema ). A recent study by Cevidanes et al ( 13 ) reported a 1% prevalence of A. reconditum in the blood of dogs from the Metropolitan Region of Chile. In contrast, our study revealed a significantly higher prevalence of 7.5% for A. reconditum .…”
Section: Discussionmentioning
confidence: 96%
“…In Chile, several studies have examined the role of dogs as reservoirs of vector-borne pathogens (11)(12)(13). However, there has been limited exploration of arthropods as vectors, especially within the Diptera order.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, they can live inside red blood cells or other blood cells and cause anaemia. In the case of Anaplasma and Ehrlichia infections, there are few studies in humans and limited studies in dogs [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Furthermore, in the case of Colombia and Latin America in general, but even globally, as mentioned, few studies have characterized, in detail, the profile of haematological alterations in canines with hemoparasitic infections, such as those mentioned, which would be helpful for veterinarians, especially in endemic areas.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the epidemiological importance that the different infections caused by hemoparasites in canines have had during the last few decades in the world, to date, there are relatively few studies in the world literature, even more so in Colombia, that have characterized the profile of the haematological alterations observed in canines with said infections [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Anaemia, thrombocytopenia, and variable cellular responses from leukopenia to lymphocytosis and monocytosis have been described in dogs with ehrlichiosis.…”
Section: Introductionmentioning
confidence: 99%